THE INFLUENCE OF ORGANIZATIONAL CULTURE THROUGH COMPETENCE, WORK MOTIVATION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. PEGADAIAN (PERSERO) OFFICE REGION VI MAKASSAR - nurhayati (Scientium Management Review, 2022)
This study aims to analyze (1) the influence of organizational culture on employee performance at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (2) the influence of organizational culture on employee competence at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (3) the influence of organizational culture on employee motivation at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (4) the influence of organizational culture on organizational commitment at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (5) the influence of organizational culture indirectly on employee performance through employee competence at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (6) the influence of organizational culture indirectly on employee performance through work motivation at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. (7) the influence of organizational culture indirectly on employee performance through organizational commitment at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. This study uses a quantitative approach. The data used is primary data. A sample of 81 respondents. These respondents are permanent employees of PT. Pegadaian (Persero) Tbk, Regional Office V1 Makassar. Data collection was carried out through observation and distribution of questionnaires and interviews. Data analysis using descriptive analysis techniques, validity and reliability tests, normality tests, linearity tests, multicollinearity tests, Heteroscedasticity Tests, Descriptive Statistical Analysis, path analysis (Path Analysis), Sobel tests and hypothesis testing (T test, F test, R2 test), and analysis Correlation, The results of the research analysis show that there is a significant partial effect of organizational culture variables on the performance of employees of PT Pegadaian (Persero) Tbk Kanwil VI Makassar. There is a significant influence on the competence of employees at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. There is a significant influence on employee motivation at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. There is a significant influence on organizational commitment at PT. Pegadaian (Persero) Regional Office (Kanwil) VI Makassar. There is a significant influence of organizational culture variables on the performance of employees of PT Pegadaian (Persero) Tbk Kanwil VI Makassar which is mediated by employee competence. There is a significant influence of organizational culture variables on the performance of PT Pegadaian (Persero) Tbk Regional Office VI Makassar which is mediated by employee motivation. There is a significant influence of organizational culture variables on the performance of PT Pegadaian (Persero) Tbk Regional Office VI Makassar which is mediated by organizational commitment.